Re-usable Survey Tools and Data for Advancing Open Science - Mboa Nkoudou, Thomas Hervé; van der Walt, Anelda; Bezuidenhout, Louise (My University, 2021)
Re-usable Survey Tools and Data for Advancing Open Science
Keywords: Survey tools; Data; Open Science